VD_FINDINFO AP / 2010 / 118 vom 5. Mai 2010 - VD Tribunal cantonal (2010)
SÛRETÉS, PROCÉDURE DE CONCILIATION | 127 CPC, 457 CPC, 91 CPC, 91 let. a CPC, 91 let. b CPC, 91 let. c CPC, 95 CPC, 97 al. 2 CPC, 97 CPC